Being new Poor in Bangladesh: Coping strategies, constraints, and trajectories - Nazneen, Sohela; Ahamed, Raihan; Aziz, Syeda Salina; Joshi, Anuradha; Loureiro, Miguel; Nampoothiri, Niranjan J.; Nur, Jahid; Sharmila, Nowshin; Ananna, Rabeena; Zaman, Shahaduz (Institute of Development Studies, 2024)
Recent research on the impact of the Covid-19 pandemic in Bangladesh reveals the struggles of millions who fell into poverty, unable to regain their pre-pandemic economic status. Drawing on qualitative panel data from 39 affected households in Khulna, this study explores the strategies employed by the new poor to recover, such as financial management, diversified livelihoods, and accessing social protections. However, constraints including limited access to loans, social protections, and gender norms hinder their efforts. Governance implications suggest a need for increased state support, reduced reliance on intermediaries, and efforts to build trust in local government to aid in poverty recovery.